2005
DOI: 10.1111/j.1365-2389.2005.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Organo‐mineral associations in sandy acid forest soils: importance of specific surface area, iron oxides and micropores

Abstract: Organo-mineral associations stabilize soil organic matter, though the mechanisms by which they do so are unclear. We used particle-size fractions < 6.3 mm of two soils to examine the importance of Fe oxides, short-range order Al silicates and the surface areas of minerals and micropores on the formation of organo-mineral associations. In the subsoil Fe oxides were most strongly statistically correlated with the mineral-bound organic carbon. We therefore assume that they are the most important substrates for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
145
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(171 citation statements)
references
References 31 publications
16
145
1
4
Order By: Relevance
“…This evolution, synchronized with an increase in OC in the B horizon, marks the beginning of podzolization from 270 to 335 years as demonstrated by the strong correlation between elementary OC and Fe DCB fluxes in the B horizons (R 2 = 0.99, n = 3, correlation significant at 1% confidence level). This correlation was already observed in other Podzols (e.g., Eusterhues et al, 2005). Once the required pH has been reached, podzolization starts within 50 years.…”
Section: Dynamics Of Fe Mobilizationsupporting
confidence: 56%
“…This evolution, synchronized with an increase in OC in the B horizon, marks the beginning of podzolization from 270 to 335 years as demonstrated by the strong correlation between elementary OC and Fe DCB fluxes in the B horizons (R 2 = 0.99, n = 3, correlation significant at 1% confidence level). This correlation was already observed in other Podzols (e.g., Eusterhues et al, 2005). Once the required pH has been reached, podzolization starts within 50 years.…”
Section: Dynamics Of Fe Mobilizationsupporting
confidence: 56%
“…In addition, Grand and Lavkulich (2012) showed that Fe and Al can form organometallic complexes with SOC. Yet, as this mechanism enables SOC stabilization, the translocation of Al and Fe in the mineral layers of Podzolic soils (dominant in coastal temperate forests of British Columbia) may enhance SOC storage (Eusterhues et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The organic matter is stabilized by physical inclusion and chemical reaction with metal oxide surfaces (Kaiser and Guggenberger, 2000;Wagai and Mayer, 2007;Kaiser and Guggenberger 2003;Eusterhues et al 2005). Various forms of iron oxides can be found in soils (Cornell and Schwertmann, 2003).…”
Section: Introductionmentioning
confidence: 99%